Bibliographic Data - Jankauskas, Rimantas (Acta medica Lituanica, 2020)
Lithuania language editor Danutė PetrauskienėEnglish language editor VTeXCover design Jurga TėvelienėLayout Vida VaidakavičienėAuthors are responsible for the content of their workVilnius University Press9 Saulėtekio Av., III Building, LT-10222 Vilniusinfo@leidykla.vu.lt, www.leidykla.vu.lt/en/Books Online knygynas.vu.ltVilnius University Press Scholarly Journals zurnalai.vu.ltPrinted by UAB „Ciklonas“68 Žirmūnų St., LT-09124 VilniusPrint run 50 copies. 4.7 author’s sheet
Keywords: none